Sufi Tradition and the Establishment of Islamic Culture - Thohir, Ajid (TAWARIKH, 2016)
ABSTRACT: Sufi tradition was born at the instigation of Islamic spirituality and reflects a new social and cultural forces in the classical period of Islam. Its configuration is not release from reality of Sufiâs âzawiyahâ as a center of their development. The presence of Sufi institutions seems to be a counterweight to the political hegemony of the caliphs Amawiyah. The role and function of âzawiyahâ from time to time have ups and downs, but its existence was maintaining intellectual and spiritual development of the Muslims. One of the unique tradition of them is writing the book on âManaqibâ or Sufi hagiography as the embodiment of ideals, intellectual, and âtarekatâ (Sufi order) institutional doctrine as a reflection cohesiveness students in raising the role of teaching and Sufis figure as well as being a great effort for the development of Islamic historiography. And proved to be much more Sufi groups that maintain the life of such, they are not crystallized in the form of a dynasty, but more concrete in the form of social religious-institutions in areas of the East Central and parts of Asia, or in the form of religious schools in the Indonesian archipelago region. Specifically, Sufism in Medieval showed very strong social forces, especially in the pockets of rural and urban areas in a number of cities of Islam. Moreover, the Islamic tradition, mosque, and Islamic boarding school in âNusantaraâ (Indonesian archipelago) are the part of the network of Sufi âzawiyahâ tradition that has long flourished in the Middle East at the middle period in the history of Islam.KEY WORDS: Civilization; Sufi Zawiyah; Social-Political Condition; Islamic Tradition; Historiography.About the Author: Dr. Ajid Thohir is a Lecturer at the Department of History and Civilization of Islam, Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. E-mail address: ajid_thohir@yahoo.comHow to cite this article? Thohir, Ajid. (2016). âSufi Tradition and the Establishment of Islamic Cultureâ in TAWARIKH: International Journal for Historical Studies, Vol.8(1) October, pp.31-44. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (June 19, 2016); Revised (August 31, 2016); and Published (October 28, 2016).